Advances in Normobaric Hyperoxia Brain Protection in Experimental Stroke - Chen, Zhiying; Ding, Yuchuan; Ji, Xunming; Meng, Ran (Frontiers in Neurology, 2020)
As we all know that stroke is still a leading cause of death and acquired disability. Etiological treatment and brain protection are equally important. This review aimed to summarize the advance of normobaric-hyperoxia (NBHO) on brain protection in the setting of experimental stroke and brain trauma. We analyzed the data from relevant studies published on PubMed Central (PMC) and EMBASE, about NBHO on brain protection in the setting of experimental ischemic and hemorrhagic strokes and brain trauma, which revealed that NBHO had important value on improving hypoxia and attenuating ischemia damage. The mechanisms of NBHO involved increasing the content of oxygen in brain tissues, restoring the function of mitochondria, enhancing the metabolism of neurons, alleviating blood-brain barrier (BBB) damage, weakening brain cell edema, reducing intracranial pressure, and improving cerebral blood flow, especially in the surrounding of injured area of the brain, to make the neurons in penumbral area alive. Compared to hyperbaric oxygen (HBO), NBHO is more safe and more easily to transform to clinical use, whereby, further studies about the safety and efficacy as well as the proper treatment protocol of NBHO on human may be still needed.